Spatial market segmentation for rice: An approach to support the development of demand-driven breeding products - Paguirigan, Neale Marvin; Laborte, Alice G.; Maunahan, Aileen; Lenaerts, Bert; Dixit, Shalabh (International Rice Research Institute, 2023)
New and improved crop varieties that are higher yielding, more nutritious, and resilient to climate shocks, pests and diseases are needed to address food insecurity, climate change and rapid transformation of the agriculture sector. Past varietal development was largely supply-driven which hampered varietal adoption by farmers. In response, the CGIAR aims to develop demand-driven breeding products guided by insights from market intelligence. Under the CGIAR Initiative on Market Intelligence, more than 400 seed product market segments (SPMS) across 24 CGIAR crops have been defined. These SPMS reflect producer (where and how the crop is grown) and end-user requirements (what the crop is used for and consumer-preferred traits) [1]. Mapping the locations of these market segments based on spatially-referenced datasets and expert opinion further improves their characterization and prioritization. We present an example of mapping market segments for rice in South and Southeast Asia.